THE ROLE OF THE ISLAMIC RELIGION IN ARCHITECTURE - Mominkhodjaeva Nilufar Fakhriddinovna (Journals Park Publishing, 2022)
This article describes the role of religion in the creation of architecture, the creation of a new style of Islam in architecture, answers to the question "What is a theory?", As well as the stages of studying the theory of Islamic architecture.
Keywords: Islam; Qur'an; mosque